Pengaruh PENGARUH STRATEGI MEMBACA NYARING BERBANTUAN BUKU ANAK BERJENJANG TERHADAP MINAT DAN KETERAMPILAN MEMBACA SISWA - Kusuma, Lilik; Sukartiningsih, Wahyu; Syafruddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Indonesia is ranked low in terms of reading literacy, both in terms of interest and reading skills. The independent learning curriculum is designed to improve students' reading literacy, one of which is through graded children's books at the elementary school level. This study was conducted to determine the effect of the reading aloud strategy assisted by graded children's books on students' reading interests and skills. This type of research is a quasi-experimental study with a sample size of 30 elementary school students in grade III in each control and experimental class. The experimental class is a class that applies the reading aloud strategy assisted by graded children's books, while the control class is a class that applies conventional learning strategies. The research instrument used to measure the reading interest variable is a questionnaire, while the reading skill variable is a reading test question. The analysis tool used is the independent sample t-test. The results of the study showed that the t-count value was 6.943 with a sig of 0.000 for the reading interest variable and the t-count value was 2.962 with a sig of 0.004 for the reading skill variable. This states that there is a difference in the average interest and reading skills of students between students who learn using the reading aloud strategy assisted by graded children's books and students who use conventional strategies. The reading aloud strategy assisted by graded children's books has an effect on students' reading interests and skills.